(untitled) (Journal of Asian Development Studies, 2024)
This study investigated the transformation of finance education in Pakistan amid the rising influence of artificial intelligence (AI) in the financial sector. Through a mixed-methods approach involving 245 finance educators, industry professionals, and students from major Pakistani universities, the research examined current curricula gaps, industry requirements, and necessary pedagogical shifts. Results indicated significant disparities between existing finance education and industry needs, with 73% of professionals identifying AI literacy as crucial for future finance graduates. The study found strong positive correlations between AI-integrated finance education and graduate employability (r = 0.78, p < 0.001). Recommendations include curriculum redesign, faculty development programs, and industry-academia partnerships to prepare finance students for an AI-driven future.